A Joint Photoelectron Spectroscopy and Theoretical Study on the Electronic Structure of UCl5− and UCl5. Issue 10 (12th July 2013) - Su, Jing; Dau, Phuong Diem; Xu, Chao‐Fei; Huang, Dao‐Ling; Liu, Hong‐Tao; Wei, Fan; Wang, Lai‐Sheng; Li, Jun
Abstract We report a combined photoelectron spectroscopic and relativistic quantum chemistry study on gaseous UCl5− and UCl5. The UCl5− anion is produced using electrospray ionization and found to be highly electronically stable with an adiabatic electron binding energy of 4.76±0.03 eV, which also represents the electron affinity of the neutral UCl5 molecule. Theoretical investigations reveal that the ground state of UCl5− has an open shell with two unpaired electrons occupying two primarily U 5f z 3<inline-graphic xlink:href="ark:/27927/pgg3hbk5n0q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and 5fxyz based molecular orbitals. The structures of both UCl5− and UCl5 are theoretically optimized and confirmed to have C4v symmetry. The computational results are in good agreement with the photoelectron spectra, providing insights into the electronic structures and valence molecular orbitals of UCl5− and UCl5. We also performed systematic theoretical studies on all the uranium pentahalide complexes UX5− (X=F, Cl, Br, I). Chemical bonding analyses indicate that the UX interactions in UX5− are dominated by ionic bonding, with increasing covalent contributions for the heavier halogen complexes.